Franchise agreement in Romania as a form to provide economic efficiency of business activity - Вдовічен, Віталій; Voroniatnikov, O. (Baltic Journal of Economic Studies, 2019)
The purpose of the article is to study the economic and legal nature of the franchise agreement in Romania. Franchising has become one of the most effective tools for economic activity and profiting in this country, and the franchising agreement is a form, in which all aspects of this activity are reflected: the rights and obligations of the parties, the price of the franchise, the duration of the franchise relations, transactions between the franchisor and the franchisee, the prohibition of competitive actions, etc. The subject of the study is the franchise agreement in Romania. Research methodology. The research is based on the use of general scientific and special-scientific methods and techniques of scientific knowledge. The dialectical method allowed us to investigate the definition of a franchise agreement in Romania and its key terms. The comparative legal method was used to compare doctrinal approaches to this issue. The statistical method was used to establish data that reflects the effectiveness of franchising activities. The method of system analysis helped to find out, in which areas of economic activity franchising is most demanded. Interpretation of the content of Romanian legal acts governing issues related to the conclusion of a franchise agreement in this country was realized with the help of the normative-dogmatic method. The system-structural method was used to study the franchise agreement in Romania as a single entity (system) with the coordinated functioning of all its elements. The methods of grouping and classifying formed the basis for separating the list of conditions, which are necessary for concluding a franchise agreement in Romania, as well as provisions that should be included in the content of this agreement. Methods of analysis and synthesis helped to study some parts of this agreement to formulate further conclusions. Practical application. The positive experience of Romania in regulating issues related to the conclusion of a franchise contract can be used for making appropriate changes to the Ukrainian legislation. Thus, in Romania, a special regulatory act (Ordinance 52/1997), which regulates the procedure for concluding this agreement, defines the rights and obligations of the parties and establishes the essential terms of the contract and the principles for its implementation, was adopted. Issues which are not regulated by the Ordinance are subject to the Civil and the Commercial Codes of the country, as well as European legislation, which sets out requirements for the prohibition of competition. Correlation/originality. This scientific work is the first research in Ukraine devoted not only to general issues of regulation of franchising activity in Europe but specifically to the franchise agreement in a separate country (in Romania) and its legal and economic peculiarities.
Keywords: franchise agreement; franchise; franchise contract; obligations